How important is the role of iterative liver direct surgery in patients with hepatocellular carcinoma for a transplant center located in an area with a low rate of deceased donation? - Pagano, Duilio; Khouzam, Simone; Magro, Bianca; Barbara, Marco; Cintorino, Davide; di Francesco, Fabrizio; Li Petri, Sergio; Bonsignore, Pasquale; Calamia, Sergio; Deiro, Giacomo; Cammà, Calogero; Canzonieri, Marco; et al. (Frontiers in Oncology, 2022)
Introduction: Hepatocellular carcinoma (HCC) accounts for nearly 90% of primary liver cancers, with estimates of over 1 million people affected by 2025. We aimed to explore the impacting role of an iterative surgical treatment approach in a cohort of HCC patients within the Milan criteria, associated with clinical risk factors on tumor recurrence (RHCC) after liver transplant (LT) and loco-regional therapies (LRT), as well as liver resection (LR) and/or microwave thermal ablation (MWTA). Methods: Retrospectively analyzed our experience performed during an 8-year period between January 2013 and December 2021 in patients treated for HCC, focusing on describing the impact on preoperative end-stage liver disease severity, oncologic staging, tumor characteristics, and surgical treatments. Results: There were 557 HCC patients treated with a first-line approach of LR and/or LRTs (n = 335) or LT (n = 222). Median age at initial transplantation was 59 versus 68 for those whose first surgical approach was LR and/or LRT. In univariate analysis with the Cox model, nodule size was the single predictor of recurrence of HCC in the post-treatment setting (HR: 1.61, 95% CI: 1.05-2.47, p=0.030). For the LRT group, we have enlightened the following clinical characteristics as significantly associated with RHCC: hepatitis B virus infection, number of HCC nodules, size of the largest nodule, serum bilirubin and international normalized ratio. Among the overall 111 patients with RHCC in the LRT group, 33 were iteratively treated with a further curative treatment (12 were treated with LR, 2 with MWTA, 3 with a combined LR-MWTA treatment and 16 underwent LT). Only one of 18 recurrent patients previously treated with LT underwent a LR. For these RHCC patients, multivariable analysis showed the protective roles of LT for primary RHCC after IDLS, of the time relapsed between the first and second IDLS treatment, and the impact of previous minimally-invasive treatment. Conclusion: Coexistence of RHCC with underlying cirrhosis increases the complexity of assessing the net health benefit of ILDS before LT. Minimally-invasive surgical therapies and time to HCC relapse should be considered as an outcome in randomized clinical trials because it has a relevant impact on tumor-free survival.